A orientação estratégica para o baixo custo na aviação comercial - Reis, Felipa Cristina Henriques Rodrigues Lopes dos, 1971- (2010)
Lusíada. Economia & empresa. - ISSN 1645-6750. - S. 2, n.10 (2010). - p. 187-203.